Use of Acellular Dermal Matrix in Postmastectomy Breast Reconstruction. Issue 4 (October 2015) - Ranganathan, Kavitha; Santosa, Katherine B.; Lyons, Daniel A.; Mand, Simanjit; Xin, Minqiang; Kidwell, Kelley; Brown, David L.; Wilkins, Edwin G.; Momoh, Adeyiza O.
<x xml:space="preserve">Abstract</x> Background: AlloDerm and FlexHD are two types of acellular dermal matrices commonly used in implant-based reconstruction. Although the use of acellular dermal matrix has revolutionized immediate breast reconstruction in the setting of breast cancer, it remains unclear which type of acellular dermal matrix is best. The purpose of this retrospective cohort study was to compare postoperative complication rates between these two types of acellular dermal matrix. Methods: The authors reviewed the records of all patients who underwent implant-based breast reconstruction at their institution between 1998 and 2013. Dependent variables of seroma, hematoma, infection, delayed wound healing, implant exposure, and return to the operating room for management of complications were recorded. Results: A total of 309 consecutive patients were identified. Of these, AlloDerm was used in 123 patients (39.8 percent) and FlexHD was used in 186 patients (60.2 percent). Most patients in the authors' cohort underwent immediate reconstruction [n = 288 (93.2 percent)], with a mean follow-up of 20.0 months. Patients receiving AlloDerm were half as likely to have major infections compared with patients receiving FlexHD (OR, 0.50; 95 percent CI, 0.16 to 1.00; p < 0.05). The rates of other complications were similar between the two groups. Conclusion: There are significantly increased odds of a major infection in patients who undergo implant-based breast reconstruction using FlexHD compared with AlloDerm. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.